2017
DOI: 10.1088/1741-4326/aa90c0
|View full text |Cite
|
Sign up to set email alerts
|

ERO modeling and sensitivity analysis of locally enhanced beryllium erosion by magnetically connected antennas

Abstract: See the author list of "Overview of the JET results in support to ITER" by X. Litaudon et al. to be published in Nucl. Fusion Special issue: overview and summary reports from the 26th FEC (Kyoto, Japan, 17-22 Oct 2016) ERO Modeling and Sensitivity Analysis of Erosion Enhanced by Magnetically Connected Antennas2 sensitivity analysis highlights a qualitative effect (i.e., change in emission patterns) of magnetic shadowing, anomalous diffusion, and inclusion of neutral fluxes and molecular release of Be. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Similar observations were made concerning stronger impurities production near the antennas and outer divertor [10]. Erosion-redeposition modelling of edge beryllium line spectroscopy of localized, ICRF sheath-enhanced emission at magnetically connected JET outer limiters was also shown to be consistent with increased local erosion [11,12]. An excellent overview of ICRF-induced plasma surface interaction was provided in [13], while a discussion about tungsten management for H-mode scenario's optimization in JET can be found in [14].…”
Section: Introductionmentioning
confidence: 54%
“…Similar observations were made concerning stronger impurities production near the antennas and outer divertor [10]. Erosion-redeposition modelling of edge beryllium line spectroscopy of localized, ICRF sheath-enhanced emission at magnetically connected JET outer limiters was also shown to be consistent with increased local erosion [11,12]. An excellent overview of ICRF-induced plasma surface interaction was provided in [13], while a discussion about tungsten management for H-mode scenario's optimization in JET can be found in [14].…”
Section: Introductionmentioning
confidence: 54%
“…Such effects are understood as arising from local rectification of these fluctuating near-fields by the plasma near the local limiters, with the resulting potential acting then on the observed (remote) limiter via magnetic connection. Erosion modeling showed that the enhanced optical emission was consistent with increased local erosion of the Be limiter surface [3,4].…”
Section: Introductionmentioning
confidence: 83%
“…As such, this sightline (coming tangentially fro the left side) would glance by the antenna side of the limiter. This made the interpretation of the measurement challenging in the limiter surface erosion effort of Refs [3,4]. The shift of this spot back onto the limiter will also be of great value to the erosion modeling of this newer set of data.…”
Section: Experimental Arrangement and Approachmentioning
confidence: 99%
“…Concerning MD data for the interactions between pure Be and D, different works have already been carried out [15][16][17] and successfully used in ERO [15,18]. However, pure Be is easy to oxidize and a beryllium oxide (BeO) layer is expected to form on top of plasma-facing components.…”
Section: Introductionmentioning
confidence: 99%